2015
DOI: 10.1158/0008-5472.can-14-2729
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Action Score of TP53 Coding Variants Is Predictive of Platinum Response in Head and Neck Cancer Patients

Abstract: TP53 is the most frequently altered gene in head and neck squamous cell carcinoma (HNSCC) with mutations occurring in over two third of cases, however, the predictive response of these mutations to cisplatin based therapy remains elusive. In the current study, we evaluate the ability of the Evolutionary Action score of TP53 coding variants (EAp53) to predict the impact of TP53 mutations on response to chemotherapy. The EAp53 approach clearly identifies a subset of high risk TP53 mutations associated with decre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 36 publications
8
115
0
Order By: Relevance
“…The Evolutionary Action Eq. 2 is thus generally solvable for coding mutation of proteins and quantifies the effect of mutations over multiple scales, spanning molecular, clinical, and population genetics effects (21)(22)(23)(24). Here, for each residue identified in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Evolutionary Action Eq. 2 is thus generally solvable for coding mutation of proteins and quantifies the effect of mutations over multiple scales, spanning molecular, clinical, and population genetics effects (21)(22)(23)(24). Here, for each residue identified in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is a key issue for genetic counseling, as the use of NGS has led to the discovery of very rare novel germline TP53 variants of unknown significance (VUS) in the normal population (27). Multiple methodologies have been developed to assess the functional effect of TP53 variants, but their specificities and sensitivities remain low for uncommon variants (28)(29)(30).…”
Section: Heterogeneity Of Tp53 Variantsmentioning
confidence: 99%
“…Although some of these classifications have improved the clinical value of TP53 status for head and neck cancer (30), breast carcinoma (41), or diffuse large B-cell lymphoma (42), no clear rationale to definitively score TP53 variants has yet been defined.…”
Section: Somatic Tp53 Mutation In Human Tumorsmentioning
confidence: 99%
“…For these types of cancers, TP53 is the most varied gene, with between 60 and 80% having a mutation. In one study that used an evolutionary action score to assess the mutations, it was found that a subset of high-risk TP53 mutations demonstrated significantly reduced in vitro and in vivo drug efficacy, making the gene a potential prognostic marker for selection of cisplatin in treatment of head and neck cancers (Osman et al 2015). In another study, the predictive efficacy of cisplatin and carboplatin was examined in triple negative breast cancer.…”
Section: Predicting Drug Efficacymentioning
confidence: 99%